Pembudayaan Ecological Citizenship di Perguruan Tinggi Melalui Pendidikan Pancasila Sebagai Upaya Mewujudkan Sustainable Campus (Studi kasus di Universitas Negeri Surabaya) - Irfany, Achmad Faried; Usmi, Rianda; Listyaningsih, Listyaningsih; Rianingsih, Kartika Dwi; Rahmatia, Asysifa Putri (Universitas Negeri Surabaya, 2024)
As a higher education institution, Universitas Negeri Surabaya (UNESA) is vital in cultivating ecological citizenship among its academic community. This is to realise one of UNESA's missions to become a sustainable campus. However, the level of environmental citizenship in UNESA to realise a sustainable campus is still low and not optimal. This study analyses the importance of acculturation ecological citizenship through Pancasila education, forms of acculturation ecological citizenship through Pancasila education, and obstacles and challenges of acculturation ecological citizenship through Pancasila education in higher education. This research method uses a qualitative approach with a case study method. Data collection techniques are observation, document study and interviews with the coordinator of Pancasila education at UNESA and Pancasila education lecturers. The study results indicate that the urgency of acculturating ecological citizenship in Pancasila education in college is critical to form students' awareness of their environmental responsibility. Then the forms of acculturation of ecological citizenship in college are through Pancasila education material with the method of Project-Based Learning. The obstacles and challenges of acculturation of environmental citizenship in Pancasila Education in higher education university policies are still personal, the role of lecturers is still not optimal, and student awareness is still low.